Analisis Viskositas Darah melalui Parameter Neutrophil Lymphocyte Ratio dan Activated Partial Thromboplastin Time sebagai Prediktor Gangguan Hemoreologi pada Pasien Diabetes Melitus Tipe 2 - Mely Purnadianti; Arshy Prodyanatasari M.Pd. (Jurnal Sintesis: Penelitian Sains, Terapan dan Analisisnya, 2026)
Type 2 diabetes mellitus (T2DM) not only causes metabolic disorders but also triggers chronic inflammation and hypercoagulation that contribute to changes in the physical properties of blood. Neutrophil Lymphocyte Ratio (NLR) as an inflammatory marker and Activated Partial Thromboplastin Time (APTT) as a coagulation parameter have the potential to reflect hemorheological disturbances that can be explained through Poiseuille's law. This study aimed to analyze the correlation between NLR and APTT and interpret it from a biophysical perspective. A cross-sectional study involved 21 T2DM patients at Mojowarno Christian Hospital, Jombang. NLR examination used a Mindray BC-5380 hematology analyzer and APTT used a CoaDATA 501 coagulometer. Results showed mean NLR of 3.43 (33% increased) and APTT of 30.40 seconds (95% normal). Spearman Rank correlation test showed no significant relationship between NLR and APTT (r=0.272; p=0.234). Although not statistically correlated, biophysically both parameters independently contribute to increased blood viscosity which, according to Poiseuille's law, will decrease blood flow rate and increase the risk of vascular complications. Direct viscosity measurement is needed for empirical confirmation. This study underscores the importance of a multidisciplinary approach in understanding the pathophysiology of T2DM.